Flashover occurrence factor of insulator string with arc horn on high voltage transmission line - Weerachai Naon (2018)
This paper describes the occurrence of flashover on insulator surface instead of between the arc horn gap on unbalance insulation double circuit high voltage transmission line, whose lower insulation side has arc horn attach at each insulator strings. Front time and amplitude of lightning strokes and interception point of lightning flash were the main factors of this study. The simulations were performed with PSCAD/EMTDC. The main conclusion from the simulation results presented in this paper is only in the case of shielding failure the steepness of wave front and the lightning current magnitude increases, the tendency of insulator surface flashover increases.